Exploring Physical Prototyping Techniques for Functional Devices using .NET Gadgeteer - Hodges, Steve; Taylor, Stuart; Villar, Nicolas; Scott, James; Helmes, John (Proceedings of TEI 2013, 2013)
In this paper we present a number of different physical construction techniques for prototyping functional electronic devices. Some of these approaches are already well established whilst others are more novel; our aim is to briefly summarize some of the main categories and to illustrate them with real examples. Whilst a number of different tools exist for building working device prototypes, for consistency the examples we present here are all built using the Microsoft .NET Gadgeteer platform. Although this naturally constrains the scope of this study, it also facilitates a basic comparison of the different techniques. Our ultimate aim is to enable others in the field to learn from our experiences and the techniques we present.